GAMBARAN TINGKAT PENGETAHUAN & SIKAP IBU TENTANG IMUNISASI DASAR - Arifatun Nisaa (Jurnal Manajemen Informasi dan Administrasi Kesehatan, 2018)
One way that can be done, to eliminate the bad view of immunization is to increase the knowledge and attitudes of mothers about the benefits of basic immunization, which in turn will change the behavior of mothers towards basic immunization. This can be improved, by doing health promotion about basic immunization with the right media. Print media (leaflets) are generally widely used in the process of health promotion so that the delivery of information is more acceptable to the target because it can foster interest or interest in the target with the contents of the message delivered. The purpose of this study was to describe the level of knowledge & attitudes of mothers about basic immunization in children, in Sukoharjo district. The results of the statistical test showed a p value of <0.05 (CI: 95%). There is a difference between the level of knowledge & attitudes of mothers regarding the coverage of basic immunization in children.Keywords: knowledge, attitude, basic immunization, media effectiveness